2013
DOI: 10.1007/s00256-013-1665-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of primary osteoarthritis in the ulnar aspect of the wrist and the factors that are correlated with ulnar wrist osteoarthritis: a cross-sectional study

Abstract: Primary OA of the ulnar wrist was most frequent in the DRUJ and second most frequent in the ulnolunate joint. UV correlated most with OA in the ulnar aspect of the wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
13
1
2
Order By: Relevance
“…15 But this study has several limitations. The first is that several participants enrolled in this study had some type of wrist problem without OA.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…15 But this study has several limitations. The first is that several participants enrolled in this study had some type of wrist problem without OA.…”
Section: Discussionmentioning
confidence: 91%
“…The relation between UV and age was the same as reported by Nakamura et al 14 Our results showed that UV increased and RI decreased with age were consistent with previous reports. 15 , 21 Using Pearson's coefficient, Katayama et al 15 analysed eight parameters (sex, age, RI, UV, CHR, VT, RLA, RSA) and the presence or absence of OA at the ulnar wrist joint. They then performed a multivariate logistic regression analysis, which revealed that UV had the highest significant correlation with OA of the DRUJ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La artrosis de la ARCD puede deberse, al igual que en otras áreas anatómicas, tanto a causas primarias como a causas secundarias. La artrosis primaria es más común en mujeres y se asocia con una varianza cubital positiva 1 . Las causas secundarias son muy numerosas, pero tienen como denominador común la incongruencia y/o la inestabilidad de la articulación como resultado de agresiones directas o indirectas (fracturas de extremidad distal del radio, lesiones de los ligamentos radiocubitales distales, infecciones, artritis reumatoide, etc.…”
Section: Introductionunclassified